Agro-industrial residue from starch extraction of Pachyrhizus ahipa as filler of thermoplastic corn starch films. (10th December 2015) - López, O.V.; Versino, F.; Villar, M.A.; García, M.A.
Highlights: Fibrous residue from P. ahipa starch extraction (PASR) was used as film filler. Biocomposite TPS-films were obtained by melt-mixing and compression molding. An integral microscopic structure characterization of biocomposite was performed. Reinforced films showed lower water vapor permeability. Fibrous filler lead to more resistant matrices improving their mechanical properties. Abstract: Biocomposites films based on thermoplastic corn starch (TPS) containing 0.5% w/w fibrous residue from Pachyrhizus ahipa starch extraction (PASR) were obtained by melt-mixing and compression molding. PASR is mainly constituted by remaining cell walls and natural fibers, revealed by Scanning Electron Microscopy (SEM). Chemical composition of the residue indicated that fiber and starch were the principal components. Biocomposites thermo-stability was determined by Thermo-Gravimetric Analysis. A continuous PASR-TPS interface was observed by SEM, as a result of a good adhesion of the fibrous residue to starch matrix. Likewise, films containing PASR presented fewer superficial cracks than TPS ones, whereas their fracture surfaces were more irregular. Besides, the presence of PASR increased starch films roughness, due to fibers agglomerates. Films reinforced with PASR showed significantly lower water vapor permeability (WVP). In addition, PARS filler increased maximum tensile strength and Young's modulus of TPS films, thus leading to more resistant starch matrixes.